(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article, the factors underlying the development of the meaning of the word, the formation of polysemous words, and the semantic branching are studied. Comparative analyzes of the phenomena of polysemy and polyfunction are given. The importance of the discursive-synergistic approach in their research is highlighted.